2016
DOI: 10.1073/pnas.1602582113
|View full text |Cite
|
Sign up to set email alerts
|

Plastidial metabolite MEcPP induces a transcriptionally centered stress-response hub via the transcription factor CAMTA3

Abstract: The general stress response (GSR) is an evolutionarily conserved rapid and transient transcriptional reprograming of genes central for transducing environmental signals into cellular responses, leading to metabolic and physiological readjustments to cope with prevailing conditions. Defining the regulatory components of the GSR will provide crucial insight into the design principles of early stressresponse modules and their role in orchestrating master regulators of adaptive responses. Overaccumulation of methy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
98
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(101 citation statements)
references
References 35 publications
3
98
0
Order By: Relevance
“…The MEP pathway is a key biosynthetic route responsible for the synthesis of essential compounds and signals that modulate developmental and stress responses (Bouvier et al, 2005;Umehara et al, 2008;Hemmerlin et al, 2012;Walley et al, 2015;Benn et al, 2016). Also, several of the MEP pathway products have importance for human health and nutrition.…”
Section: Discussionmentioning
confidence: 99%
“…The MEP pathway is a key biosynthetic route responsible for the synthesis of essential compounds and signals that modulate developmental and stress responses (Bouvier et al, 2005;Umehara et al, 2008;Hemmerlin et al, 2012;Walley et al, 2015;Benn et al, 2016). Also, several of the MEP pathway products have importance for human health and nutrition.…”
Section: Discussionmentioning
confidence: 99%
“…Reactive oxygen species (ROS), formed during photosynthesis (Leister, 2017) or redox-dependent signaling, reprograms cellular transcriptome by upregulating a series of transcription factors (Br€ autigam et al, 2009;Sewelam et al, 2014). The transcription factor CAMTA4 mediates transcriptional activation of a stress-responsive cis element by methylerythritol cyclodiphosphate (MEcPP), a signaling molecule from the isoprenoid biosynthetic pathway (Benn et al, 2016;Xiao et al, 2012), whereas the transcription factor ABI4 has been identified as a critical hub that links multiple retrograde signals to transcriptional regulation of nuclear gene expression (Koussevitzky et al, 2007). Some transcription factors, such as PTM (Sun et al, 2011) and Whirly transcription factors (Foyer et al, 2014), can act as retrograde signals themselves and, upon translocation to the nucleus, directly regulate gene transcription.…”
Section: Introductionmentioning
confidence: 99%
“…In the comparative analysis of RNA-seq data from two chlorosis models, we also found that GO terms of “ERAD pathways” and “response to ER stress” were specifically enriched in i-hpHSP90C plants ( Supplementary Figure S5A,B ). A retrograde signal molecule, methylerythritol cyclodiphosphate, and SA reportedly activate the unfolded protein response (UPR) [ 37 , 38 , 39 , 40 ]. However, the role of UPR pathway in chlorosis development remains to be studied.…”
Section: Discussionmentioning
confidence: 99%